Tech SEO guide : a reference guide for developers and marketers involved in technical SEO - Edgar, Matthew (Apress Media LLC, 2023)
Tech SEO Guide provides a reference for everyone who works on the technical side of SEO. SEO has always had a technical component but over the last several years, the technical challenges are increasing as websites deliver richer and more engaging experiences. Those experiences can make it harder for Google to crawl a website and rank a website in search results. Given how important organic search rankings can be for a websites traffic, it is more important than ever to make sure the technical fundamentals are in place to support a websites SEO performance. SEO professionals includes marketers, developers, programmers, UX professionals, designers, and business executives because technical SEO impacts and overlaps with so many different areas of a business. Because the book addresses a wider audience, it provides technical details but also includes higher-level discussions about how search engines and robots work too. There are many different aspects of technical SEO and it is difficult to keep track of every detail, especially for people who only work on technical SEO matters on an occasional basis. Because of that, this guide book can be read all at once for those wanting to study technical SEO in detail or it can be read a paragraph at a time, allowing people to refer back to quickly jog their memory or review a complex topic. Each chapter walks through a different area of technical SEO, addressing specific scenarios and questions about that particular area. After discussing each section, the chapter will conclude with a summary of the important items to measure and monitor related to that section. What You Will Learn What factors to keep in mind as you begin a redesign of the website How to evaluate technical factors to see if a technical configuration is causing traffic to drop How to perform regular audits of a website to identify problems or areas of opportunity Who This Book is For Marketers, developers, programmers, UX professionals, designers, and business executives.